Differentiating the Personalized Information of the Physician-Patient Communication for the Chronic Obstructive Pulmonary Disease with General Probabilistic Vector Linguistic Terms. (21st November 2019) - Zhai, Yuling; Xu, Zeshui; Ren, Peijia
Abstract : To accurately determine the follow-up therapeutic schedules for the chronic obstructive pulmonary disease (COPD) patients, this paper aims to develop the analysis tools for the linguistic evaluation to improve the quality of the physician-patient communication. Firstly, we define the general probabilistic vector linguistic term (GPVLT), which is effective to depict people's judgements from different sources. Then, we establish the multigranularity linguistic space and discuss the different forms of the probabilistic vector linguistic units (PVLUs) in it. Later on, we propose the nondirectional and the directional potentials of PVLUs, which can grasp the fuzziness and the development direction of the linguistic evaluations, respectively. Last but not least, the cases about the physician-patient communication for COPD and some comparisons with the other related methods are provided to illustrate the effectiveness and practicability of the PVLUs' potentials.